IMMU-11. SPATIOTEMPORAL IMMUNOGENOMIC ANALYSIS OF THE T-CELL REPERTOIRE IN IDH-MUTANT LOWER GRADE GLIOMAS. (11th November 2019) - Zhang, Michael; Hilz, Stephanie; Martin, Michael; Hong, Chibo; Yu, Yao; Bollam, Saumya; Grimmer, Matthew; Looney, Timothy; Lowman, Geoffrey; Ganpule, Gauri; Phillips, Joanna; Shai, Anny; et al.
Abstract: The design and evaluation of immunotherapies in IDH -mutant lower grade gliomas (LGG) is hindered by a poor understanding of the LGG T-cell repertoire. We present data on the temporal evolution, intratumoral spatial distribution, and prognostic value of the T-cell repertoire in IDH -mutant LGGs. We performed immunogenomic profiling using T-cell receptor beta-chain sequencing of 163 glioma and peripheral blood samples from 33 immunotherapy-naive glioma patients (22 astrocytomas, 11 oligodendrogliomas). T-cell repertoire evolution was analyzed in a subset of 26 patients (69 samples) with matched primary (WHO grade II) and recurrent (WHO grade II-IV) glioma samples. T-cell repertoire diversity was defined as the number of unique T-cell clonotypes by V-gene, J-gene, and CDR3 nucleotide sequences. Malignant transformed (Grade III or IV) recurrent gliomas demonstrated increased T-cell repertoire diversity compared to their patient-matched primary tumors (p=0.0023), but grade II recurrences did not show the same increased diversity (p=0.26). This increase in T-cell repertoire diversity was greater in patients who underwent transformation in the context of TMZ-associated hypermutation compared to spontaneously transformed counterparts (p=0.035). In grade II primary astrocytomas (n=17), T-cell repertoire diversity above the median (186 unique T-cell clonotypes per sample) was associated with worse transformation-free (HR=4.2, p=0.045) and overall survival (HR=6.4, p=0.025). Next, we evaluated intratumoral immune heterogeneity in 7 patients by sampling from up to 10 distinct and maximally-separated intratumoral sites per LGG (64 samples). Eighty-two to 96% of unique clonotypes within a given tumor were present only within a single sampled site. Despite this heterogeneity, six LGG patients harbored T-cell clonotypes present tumor-wide across all sampled sites within a given tumor. Ten of 24 (42%) tumor-wide T-cell clonotypes were enriched in the glioma compared to matched peripheral blood, suggesting glioma-specificity. Taken together, T-cell receptor profiling in LGGs may have utility both as a prognostic biomarker and to identify glioma-specific T-cells.